Variasi Sekuens Gen COI untuk DNA Barcoding Ikan Tuna - Kolondam, Beivy J (Media Teknologi Hasil Perikanan, 2020)
DNA barcoding has been used for species identification of fishes, especially for fish product authentication. In tuna fish food products authentication, DNA barcoding is needed due to its requirement of small amount of samples for species identification. The COI gene, located in mitochondria of animal cells, is established as standard marker for animal DNA barcoding. This research aimed to study the variation in COI gene of tuna fish species in three groups, such as Bluefin tuna (five species), Yellowfin tuna (three species), and other tuna species (five species). The variation comparison showed that this gene can differentiate 11 out of 13 tuna species. The Thunnus orientalis and T. thynnus has 100% similarity over COI gene (identical). Therefore, another marker gene is required to differentiate this two species. Variation in COI gene has the ability to differentiate all species in the genus Thunnus with other genus (Auxis, Euthynnus, and Katsuwonus) by 29 nucleotide sites. Bluefin tuna group has one site unique to two other groups. Yellowfin tuna group did not have site for differentiation. Other tuna species has 33 nucleotide sites for differentiation with two other groups.